Gas barrier laminate, packaging bag and package

The gas barrier laminate with a polypropylene content of 90% and a specific adhesive layer design enhances the bursting strength and oxygen barrier properties of packaging bags, addressing the limitations of polypropylene in heat-sterilized monomaterial recycling.

JP2025001761APending Publication Date: 2025-01-09TOPPAN HOLDINGS INC

Patent Information

Application Number
JP2023101413
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-21
Publication Date
2025-01-09

AI Technical Summary

Technical Problem

Packaging bags made of polypropylene face challenges in terms of bursting strength and oxygen barrier properties after heat sterilization, limiting their effectiveness in monomaterial recycling applications.

Method used

A gas barrier laminate structure is designed with a polypropylene content of 90% by mass, featuring a gas barrier layer between the second base layer and the adhesive layer, and an elastic modulus of the adhesive layer of 30 MPa or less, ensuring strong adhesion and resistance to bursting while maintaining excellent oxygen barrier properties after heat sterilization.

Benefits of technology

The laminate achieves high resistance to bursting and maintains excellent oxygen barrier properties even after heat sterilization, facilitating monomaterial recycling and suitability for applications like retort treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025001761000001_ABST
    Figure 2025001761000001_ABST
Patent Text Reader

Abstract

To provide a gas barrier laminate useful for producing a packaging bag and a package which are hardly burst, and are excellent in oxygen barrier property even after heat sterilized while achieving mono materialization.SOLUTION: A gas barrier laminate has a laminate structure which includes an intermediate layer having a second substrate layer and a gas barrier layer disposed on the surface of the second substrate layer, an adhesion layer, and a sealant layer in this order. The gas barrier laminate is such that: the gas barrier layer is positioned between the second substrate layer and the adhesion layer; the ratio of the total mass of polypropylene in the laminate is 90 mass% or more; and the elastic modulus of the adhesion layer obtained through predetermined processes (a) and (b) is 30 MPa or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a gas barrier laminate, a packaging bag, and a packaging body. [Background technology]

[0002] Gas barrier laminates are widely used as packaging materials for foods, medicines, etc., including heat sterilization such as boiling and retort treatments. In recent years, as the plastic waste problem has been attracting attention around the world, the demand for environmentally friendly packaging materials is increasing toward the realization of a recycling-oriented society. Many global companies have set goals for better plastic resource circulation for packaging materials and have come up with various measures. In addition, efforts toward recycling based on mono-materials (single materials) are accelerating worldwide. For example, in the United States, recycling routes from collection to reuse of polyethylene resins are beginning to be established.

[0003] As such a packaging material, Patent Document 1 discloses a laminate comprising a first substrate layer, a second substrate layer and a sealant layer in this order, in which the first substrate layer, the second substrate layer and the sealant layer all comprise polyolefin films, and which comprises an inorganic oxide layer at a predetermined position, and in which the thermal shrinkage rate of each layer satisfies a predetermined formula. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent Publication No. 2021-020391 Summary of the Invention [Problem to be solved by the invention]

[0005] The inventors selected polypropylene as a material to realize mono-materialization, and their investigation revealed that packaging bags using polypropylene had room for improvement in terms of both burst strength and oxygen barrier properties after heat sterilization.

[0006] One aspect of the present disclosure provides a packaging bag and a package that are made of a mono-material, are resistant to rupture, and have excellent oxygen barrier properties even after heat sterilization treatment. Another aspect of the present disclosure provides a gas barrier laminate that is useful for producing such a packaging bag and a package. [Means for solving the problem]

[0007] In order to solve the above problems, the present disclosure provides the following gas barrier laminate, packaging bag, and packaging body. [1] A first substrate layer; an intermediate layer having a second base layer and a gas barrier layer provided on a surface of the second base layer; An adhesive layer; A sealant layer; A gas barrier laminate having a layered structure comprising the above in this order, the gas barrier layer is located between the second base layer and the adhesive layer, The total mass ratio of polypropylene in the laminate is 90 mass% or more, A gas barrier laminate, wherein the adhesive layer has an elastic modulus of 30 MPa or less, as determined through the following steps (a) and (b): <Measurement of elastic modulus> (a) a step of obtaining a graph showing the relationship between the deformation amount of the adhesive layer and the load applied to the adhesive layer by measuring a force curve of the adhesive layer using a scanning probe microscope; (b) calculating the elastic modulus of the adhesive layer based on the graph and a JKR analysis model; [2] The gas barrier laminate according to [1], wherein the elastic modulus of the adhesive layer measured through the above steps (a) and (b) after carrying out heating and pressure treatment under conditions of a temperature of 128°C, a time of 15 minutes, and a pressure of 0.3 MPa is 50 MPa or less. [3] The gas barrier laminate according to [1] or [2], wherein the gas barrier layer has a barrier coat layer. [4] The gas barrier laminate according to [3], wherein the gas barrier layer has, from the second substrate layer side, an anchor coat layer, a vapor deposition layer, and the barrier coat layer in this order. [5] The gas barrier laminate according to [4], wherein the thickness of the vapor deposition layer is 5 nm or more and 80 nm or less. [6] When the first base layer is heated in an oven at 150°C for 15 minutes, the MD heat shrinkage calculated by the following formula (1) is 7% or less, and the TD heat shrinkage calculated by the following formula (2) is 5% or less, The gas barrier laminate according to any one of [1] to [5], wherein when the sealant layer is heated in an oven at 150° C. for 15 minutes, the MD heat shrinkage rate calculated by the following formula (1) is 0.4% or less. MD heat shrinkage rate (%) = (MD length before heating - MD length after heating) / MD length before heating × 100 ... (1) TD heat shrinkage rate (%) = (TD length before heating - TD length after heating) / TD length before heating × 100 ... (2) [7] The gas barrier laminate according to any one of [1] to [6], wherein the adhesive layer has a thickness of 0.5 μm or more and 10 μm or less. [8] The first base layer and the second base layer are stretched polypropylene films, The gas barrier laminate according to any one of [1] to [7], wherein the sealant layer is a non-oriented polypropylene film. [9] A packaging bag formed using the gas barrier laminate according to any one of [1] to [8].

[10] The packaging bag described in [9], which is used for applications requiring heat treatment at 80°C or higher.

[11] A packaging bag and contents contained in the packaging bag. The packaging bag is formed using a laminate, the laminate has a laminate structure including, in this order, a first base material layer, an intermediate layer having a second base material layer and a gas barrier layer provided on a surface of the second base material layer, an adhesive layer, and a sealant layer; The total mass ratio of polypropylene in the laminate is 90 mass% or more, A package, wherein the adhesive layer has an elastic modulus of 50 MPa or less, as determined through the following steps (a) and (b): <Measurement of elastic modulus> (a) a step of obtaining a graph showing the relationship between the deformation amount of the adhesive layer and the load applied to the adhesive layer by measuring a force curve of the adhesive layer using a scanning probe microscope; (b) calculating the elastic modulus of the adhesive layer based on the graph and a JKR analysis model; Effect of the Invention

[0008] According to one aspect of the present disclosure, there is provided a packaging bag and a package that are mono-material, are resistant to rupture, and have excellent oxygen barrier properties even after heat sterilization treatment. According to another aspect of the present disclosure, there is provided a gas barrier laminate that is useful for producing such a packaging bag and a package. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a schematic cross-sectional view showing a gas barrier laminate according to one embodiment. [Diagram 2] FIG. 2 is a schematic front view of an example of a packaging bag. [Diagram 3] FIG. 3 is a schematic diagram showing a method for measuring the thermal shrinkage rate during heating in an oven. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, embodiments of the present disclosure will be described. Note that the same components are given the same reference numerals and duplicated explanations will be omitted. Furthermore, the dimensional ratios in the drawings are not limited to the ratios shown in the drawings.

[0011] <Gas barrier laminate> A gas barrier laminate according to one embodiment will be described below. FIG. 1 is a schematic cross-sectional view showing the laminate according to this embodiment. The laminate 1 has a laminate structure including a first base material layer 10, a first adhesive layer 20, a second base material layer 31, an intermediate layer 30 having a gas barrier layer 32 provided on the surface of the second base material layer 31, a second adhesive layer 40, and a sealant layer 50, in this order. The gas barrier layer 32 is located between the second base material layer 31 and the second adhesive layer 40. The total mass ratio of polypropylene in the laminate 1 is 90 mass% or more. The elastic modulus of the second adhesive layer 40 obtained through the following steps (a) and (b) is 30 MPa or less.

[0012] <Measurement of elastic modulus> (a) A step of obtaining a graph showing the relationship between the deformation amount of the second adhesive layer and the load applied to the second adhesive layer by measuring a force curve of the second adhesive layer using a scanning probe microscope. (b) calculating the elastic modulus of the second adhesive layer based on the graph and the JKR analysis model;

[0013] The laminate 1 is useful for manufacturing a packaging bag that is not easily broken and has excellent oxygen barrier properties even after heat sterilization while being made into a mono-material. The inventors speculate as follows about the reason why such an effect is achieved. Polypropylene has a property that the surface layer is easily peeled off. Therefore, a laminate containing polypropylene has a tendency to have a weaker strength between the base layers and a lower burst strength than a laminate composed of a multi-material. By disposing a gas barrier layer between the second base layer and the second adhesive layer, the adhesion between the intermediate layer and the sealant layer is increased, the above-mentioned surface peeling is suppressed, and the strength between the base layers is increased. This allows the internal pressure applied to the sealant layer when the laminate is made into a packaging bag to be distributed throughout the entire laminate. As a result, the packaging bag is not easily broken.

[0014] However, when a gas barrier layer is disposed between the second base layer and the second adhesive layer, a new problem occurs in that the oxygen barrier property is easily deteriorated by heat sterilization. To address this problem, the elastic modulus of the second adhesive layer is set to 30 MPa or less, thereby mitigating the effect of shrinkage of each layer during heat sterilization. As a result, the laminate is useful for producing a packaging bag that is less likely to burst and has excellent oxygen barrier property even after heat sterilization.

[0015] If a gas barrier layer is disposed between the second base layer and the first adhesive layer, the adhesion between the sealant layer 50 and the intermediate layer 30 becomes insufficient. If the adhesion is insufficient, when pressure is applied from inside the packaging bag, the second base layer is likely to peel off from the second adhesive layer due to the internal pressure. Therefore, stress is concentrated in the sealant layer 50, making it prone to cracks. If a gas barrier layer is disposed between the second base layer and the first adhesive layer, the adhesion to the second adhesive layer 40 tends to be weaker, especially when the second base layer 31 is a resin film with low polarity.

[0016] [First base layer 10] The first base layer 10 is a plastic member that functions as the outermost layer in the laminate 1. The thickness of the first base layer 10 is not particularly limited. Depending on the application, the thickness can be set to 6 to 200 μm, but from the viewpoint of reducing materials to reduce the environmental load and from the viewpoint of obtaining excellent heat resistance, impact resistance, and excellent gas barrier properties, the thickness may be 9 to 50 μm, 12 to 38 μm, 18 to 30 μm, or 15 to 30 μm.

[0017] From the viewpoint of recycling suitability of the laminate 1, the first base layer 10 is, for example, a polyolefin film. The first base layer 10 may contain a polypropylene film or may be made of a polypropylene film. The polypropylene film may be an acid-modified polypropylene film obtained by graft-modifying polypropylene with an unsaturated carboxylic acid, an acid anhydride of an unsaturated carboxylic acid, an ester of an unsaturated carboxylic acid, or the like. In addition, as the polypropylene, a polypropylene-based resin such as a homopolypropylene resin (PP), a propylene-ethylene random copolymer, a propylene-ethylene block copolymer, or a propylene-α-olefin copolymer may be used.

[0018] The polypropylene film constituting the first base layer 10 may contain various additives such as a flame retardant, a slip agent, an antiblocking agent, an antioxidant, a light stabilizer, a tackifier, and an antistatic agent.

[0019] The polypropylene film constituting the first base layer 10 may be a stretched film or a non-stretched film. However, from the viewpoints of impact resistance, heat resistance, water resistance, dimensional stability, etc., the polypropylene film is preferably a stretched polypropylene film. This can prevent the first base layer 10 from being thermally fused in the heat sealing process during bag making. In addition, the laminate 1 can be more suitably used for applications in which heat treatment such as retort treatment and boiling treatment is performed. The stretching method is not particularly limited, and any method may be used as long as a dimensionally stable film can be supplied, such as stretching by inflation, uniaxial stretching, or biaxial stretching.

[0020] When the first base layer is oven-heated under conditions of 150°C for 15 minutes, the MD heat shrinkage calculated by the following formula (1) is preferably 7% or less, and the TD heat shrinkage calculated by the following formula (2) is preferably 5% or less. If the shrinkage ratio is within the above range, the oxygen barrier property after retort treatment tends to be further improved. From the same viewpoint, the MD heat shrinkage ratio is more preferably 5% or less, and even more preferably 4% or less. From the same viewpoint, the TD heat shrinkage ratio is more preferably 4% or less. The MD heat shrinkage ratio may be, for example, 1% or more. The TD heat shrinkage ratio may be, for example, 0.4% or more.

[0021] MD heat shrinkage rate (%) = (MD length before heating - MD length after heating) / MD length before heating × 100 ... (1) TD heat shrinkage rate (%) = (TD length before heating - TD length after heating) / TD length before heating × 100 ... (2)

[0022] MD is the machine direction of the base layer and the sealant layer, and TD is the transverse direction. The orientation angle of the film can be measured using, for example, a retardation measuring device (product name: KOBRA, manufactured by Oji Scientific Instruments Co., Ltd.), and MD and TD can be distinguished from the orientation angle. When the film is a stretched polypropylene film, the direction in which the molecular chains are oriented is considered to be TD.

[0023] The lamination surface of the first base material layer 10 may be subjected to various pretreatments such as corona treatment, plasma treatment, and flame treatment, or may be provided with a coating layer such as an easy-adhesion layer.

[0024] [First adhesive layer 20 and second adhesive layer 40] The first adhesive layer 20 is a layered member that bonds the first base layer 10 and the second base layer 31. The second adhesive layer 40 is a layered member that bonds the gas barrier layer 32 and the sealant layer 50. For example, polyester-isocyanate resin, urethane resin, polyether resin, etc. can be used as the adhesive material contained in the first adhesive layer 20 and the second adhesive layer 40. To use the packaging bag for retort applications, a two-liquid curing urethane adhesive that is resistant to retort can be preferably used. When the adhesive is a urethane adhesive, the second adhesive layer 40 tends to have a high adhesion to the gas barrier layer 32, which has a highly polar surface. As a result, the resulting packaging bag tends to have even better burst strength. From the viewpoint of environmental consideration, the adhesive does not need to contain 3-glycidyloxypropyltrimethoxysilane (GPTMS). The first adhesive layer 20 and the second adhesive layer 40 do not need to contain chlorine. In this case, the first adhesive layer 20 and the second adhesive layer 40 can suppress coloration of the recycled resin after recycling and odor generation due to heat treatment. From the viewpoint of environmental consideration, the first adhesive layer 20 may be formed of a biomass material and may not contain a solvent.

[0025] The urethane adhesive contains polyol and polyisocyanate. When a urethane adhesive is used, the first adhesive layer 20 and the second adhesive layer 40 may contain polyurethane obtained by curing the urethane adhesive, or may contain an uncured urethane adhesive.

[0026] The polyol has two or more hydroxyl groups in one molecule. The polyisocyanate has two or more isocyanate groups in one molecule. The polyol and the polyisocyanate may react as a base resin and a curing agent, respectively, to produce polyurethane.

[0027] The polyol may contain at least one selected from the group consisting of polyester polyols and polyether polyols.

[0028] The polyisocyanate may be used alone or in combination of two or more thereof. Examples of the polyisocyanate include an aliphatic polyisocyanate compound, an alicyclic polyisocyanate compound, and an aromatic polyisocyanate compound.

[0029] Examples of the aliphatic polyisocyanate compound include hexamethylene diisocyanate (HDI) and xylylene diisocyanate (XDI). Examples of the alicyclic polyisocyanate compound include isophorone diisocyanate (IPDI). Examples of the aromatic polyisocyanate compound include tolylene diisocyanate (TDI) and diphenylmethane diisocyanate (MDI). The polyisocyanate compound may also be a multimer (e.g., a trimer) of these compounds, and specifically, an adduct, a biuret, an isocyanurate, or the like may be used. The polyisocyanate is preferably a polymer of hexamethylene diisocyanate, since the resulting packaging bag tends to have better oxygen barrier properties after retort treatment.

[0030] The mass ratio of polyol to polyisocyanate (polyol:polyisocyanate) is preferably 5:1 to 15:1, and more preferably 6:1 to 8:1.

[0031] The temperature at which the urethane adhesive is cured is preferably 40 to 60°C, and more preferably 40 to 50°C.

[0032] The time for curing the urethane adhesive is preferably 72 to 168 hours, and more preferably 72 to 120 hours.

[0033] The thickness of the first adhesive layer 20 is, for example, 0.5 μm or more and 10 μm or less. When the thickness of the first adhesive layer 20 is 0.5 μm or more, peeling between the first base material layer 10 and the second base material layer 31 can be effectively suppressed. When the thickness of the first adhesive layer 20 is 10 μm or less, the laminate 1 can be easily made into a mono-material (details will be described later). The thickness of the first adhesive layer 20 may be 1 μm or more, 2 μm or more, 8 μm or less, 6 μm or less, or 5 μm or less.

[0034] The thickness of the second adhesive layer 40 is, for example, 0.5 μm or more and 10 μm or less. When the thickness of the second adhesive layer 40 is 0.5 μm or more, peeling between the gas barrier layer 32 and the sealant layer 50 can be effectively suppressed. When the thickness of the second adhesive layer 40 is 10 μm or less, the laminate 1 can be easily made into a mono-material (details will be described later). The thickness of the first adhesive layer 20 may be 1 μm or more, 2 μm or more, 8 μm or less, 6 μm or less, or 5 μm or less.

[0035] The elastic modulus of the first adhesive layer 20 may be 30 MPa or less, 25 MPa or less, or 20 MPa or less. The elastic modulus of the first adhesive layer 20 may be 5 MPa or more. The elastic modulus of the first adhesive layer 20 is determined by the same method as the elastic modulus of the second adhesive layer 40.

[0036] The elastic modulus of the second adhesive layer 40 is 30 MPa or less, and is preferably 25 MPa or less because it has better oxygen barrier properties even after heat sterilization. The elastic modulus of the second adhesive layer 40 may be 5 MPa or more. The elastic modulus of the second adhesive layer 40 is determined through the following steps (a) and (b).

[0037] <Measurement of elastic modulus> (a) A process for obtaining a graph showing the relationship between the deformation amount of the adhesive layer and the load applied to the adhesive layer by measuring the force curve of the adhesive layer using a scanning probe microscope. (b) A process of calculating the elastic modulus of the adhesive layer based on the graph and the JKR analysis model

[0038] The elastic modulus of the first adhesive layer 20 and the second adhesive layer 40 can be adjusted by changing the components of the adhesive, the ratio of the base agent to the curing agent, and the curing time and temperature.

[0039] The elastic modulus of the first adhesive layer 20 after the heating and pressurizing treatment is performed under the conditions of a temperature of 128°C, a time of 15 minutes, and a pressure of 0.3 MPa may be 20 MPa or less, 15 MPa or less, or 12 MPa or less. The elastic modulus of the first adhesive layer 20 after the heating and pressurizing treatment is performed under the above conditions may be 5 MPa or more. The elastic modulus of the first adhesive layer 20 after the heating and pressurizing treatment is performed under the above conditions is determined by the same method as the elastic modulus of the second adhesive layer 40.

[0040] The elastic modulus of the second adhesive layer 40 after the heating and pressurizing treatment under the conditions of a temperature of 128°C, a time of 15 minutes, and a pressure of 0.3 MPa tends to be even more excellent in oxygen barrier properties even after the heat sterilization treatment, so that the elastic modulus of the second adhesive layer 40 is preferably 50 MPa or less, more preferably 30 MPa or less, and even more preferably 25 MPa or less. The elastic modulus of the second adhesive layer 40 after the heating and pressurizing treatment under the above conditions may be 5 MPa or more. The elastic modulus of the second adhesive layer 40 after the heating and pressurizing treatment under the above conditions is determined by the same method as the elastic modulus of the second adhesive layer 40.

[0041] [Middle layer 30] 1, the intermediate layer 30 has a second base layer 31 and a gas barrier layer 32. The gas barrier layer 32 exhibits gas barrier properties against gases such as water vapor and oxygen. The gas barrier layer 32 has, from the second base layer 31 side, an anchor coat layer 32a, a deposition layer 32b, and a barrier coat layer 32c in this order.

[0042] (Second base layer 31) The thickness of the second base layer 31 may be the same as that of the first base layer 10. The second base layer 31 is, for example, a polyolefin film from the viewpoint of the recyclability of the laminate 1. The second base layer 31 may contain a polypropylene film or may be made of a polypropylene film. The polypropylene film may be the same as that of the first base layer 10. The polypropylene film may be added with various additives similar to those of the first base layer 10. The second base layer 31 may be subjected to various pretreatments similar to those of the first base layer 10, or may be provided with a coating layer.

[0043] When the second base layer is oven-heated under conditions of 150°C and 15 minutes, the MD heat shrinkage calculated by the above formula (1) is preferably 10% or less, and the TD heat shrinkage calculated by the above formula (2) is preferably 12% or less. If the shrinkage is within the above range, the oxygen barrier property after retort treatment tends to be further improved. From the same viewpoint, the MD heat shrinkage is more preferably 7% or less, and even more preferably 6% or less. From the same viewpoint, the TD heat shrinkage is more preferably 10% or less, and even more preferably 9% or less. The MD heat shrinkage may be, for example, 1% or more. The TD heat shrinkage may be, for example, 0.4% or more.

[0044] (Anchor coat layer 32a) The anchor coat layer 32a functions as a layer capable of improving the adhesion performance of the deposition layer 32b on the second base layer 31, and is provided directly on the second base layer 31. Therefore, the anchor coat layer 32a is located between the second base layer 31 and the deposition layer 32b. By providing the anchor coat layer 32a, the smoothness of the surface on which the deposition layer 32b is provided in the intermediate layer 30 can be improved. In addition, the improved smoothness makes it easier to form the deposition layer 32b uniformly without defects, and makes it easier to exhibit high barrier properties. The anchor coat layer 32a can be formed, for example, using an anchor coat agent.

[0045] Examples of the anchor coating agent include polyester-based polyurethane resins, polyether-based polyurethane resins, etc. As the anchor coating agent, polyester-based polyurethane resins are preferred from the viewpoints of heat resistance and interlayer adhesive strength.

[0046] The thickness of the anchor coat layer 32a is not particularly limited, but is preferably in the range of 0.01 to 5 μm, more preferably in the range of 0.03 to 3 μm, and particularly preferably in the range of 0.05 to 2 μm. If the thickness of the anchor coat layer 32a is equal to or greater than the lower limit, a more sufficient interlayer adhesive strength tends to be obtained, whereas if the thickness is equal to or less than the upper limit, the desired gas barrier properties tend to be easily exhibited.

[0047] The method for applying the anchor coat layer 32a onto the second base layer 31 can be any known application method without any particular limitation, and examples of such methods include an immersion method (dipping method), a method using a spray, a coater, a printer, a brush, etc. Examples of the types of coaters and printers used in these methods and the application methods thereof include gravure coaters such as direct gravure method, reverse gravure method, kiss reverse gravure method, and offset gravure method, reverse roll coaters, microgravure coaters, coaters combined with chamber doctor, air knife coaters, dip coaters, bar coaters, comma coaters, die coaters, etc.

[0048] The coating amount of the anchor coat layer 32a is 1 m 2 after the anchor coat agent is applied and dried. 2 Mass per unit is 0.01 to 5 g / m 2 It is preferable that the thickness is 0.03 to 3 g / m 2 It is more preferable that the thickness of the anchor coating agent is 1m after it is applied and dried. 2 When the mass per unit area is equal to or greater than the lower limit, the film tends to be sufficiently formed, whereas when the mass per unit area is equal to or less than the upper limit, the film tends to be sufficiently dried and the solvent is less likely to remain.

[0049] The method for drying the anchor coat layer 32a is not particularly limited, but examples thereof include a method of natural drying, a method of drying in an oven set at a predetermined temperature, and a method using a dryer attached to the coater, such as an arch dryer, a floating dryer, a drum dryer, an infrared dryer, etc. Furthermore, the drying conditions can be appropriately selected depending on the drying method, and for example, in the method of drying in an oven, it is preferable to dry at a temperature of 60 to 100°C for about 1 second to 2 minutes.

[0050] As the anchor coat layer 32a, a polyvinyl alcohol resin can be used instead of the polyurethane resin. The polyvinyl alcohol resin may be any resin having a vinyl alcohol unit formed by saponifying a vinyl ester unit, such as polyvinyl alcohol (PVA) or ethylene-vinyl alcohol copolymer (EVOH).

[0051] Examples of PVA include resins obtained by homopolymerizing vinyl esters such as vinyl acetate, vinyl formate, vinyl propionate, vinyl valerate, vinyl caprate, vinyl laurate, vinyl stearate, vinyl pivalate, and vinyl versatate, followed by saponification. PVA may be modified PVA that has been copolymerized or post-modified. Modified PVA can be obtained, for example, by copolymerizing a vinyl ester with an unsaturated monomer copolymerizable with the vinyl ester, followed by saponification. Examples of unsaturated monomers copolymerizable with vinyl ester include olefins such as ethylene, propylene, isobutylene, α-octene, α-dodecene, and α-octadecene; hydroxyl-containing α-olefins such as 3-buten-1-ol, 4-pentyn-1-ol, and 5-hexen-1-ol; unsaturated acids such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, maleic anhydride, itaconic acid, and undecylenic acid; nitriles such as acrylonitrile and methacrylonitrile; diacetone acrylamide, acrylonitrile, methacrylonitrile, and methacrylonitrile; and the like. amides such as arylamide and methacrylamide; olefin sulfonic acids such as ethylene sulfonic acid, allyl sulfonic acid, and methallyl sulfonic acid; vinyl compounds such as alkyl vinyl ethers, dimethylallyl vinyl ketone, N-vinylpyrrolidone, vinyl chloride, vinyl ethylene carbonate, 2,2-dialkyl-4-vinyl-1,3-dioxane, glycerin monoallyl ether, and 3,4-diacetoxy-1-butene; vinylidene chloride, 1,4-diacetoxy-2-butene, and vinylene carbonate.

[0052] The polymerization degree of PVA is preferably 300 to 3000. If the polymerization degree is less than 300, the barrier property is likely to decrease, and if it exceeds 3000, the viscosity is too high and the coating suitability is likely to decrease. The saponification degree of PVA is preferably 90 mol% or more, more preferably 95 mol% or more, and even more preferably 99 mol% or more. The saponification degree of PVA may be 100 mol% or less, or 99.9 mol% or less. The polymerization degree and saponification degree of PVA can be measured according to the method described in JIS K 6726 (1994).

[0053] EVOH is generally obtained by saponifying a copolymer of ethylene and an acid vinyl ester such as vinyl acetate, vinyl formate, vinyl propionate, vinyl valerate, vinyl caprate, vinyl laurate, vinyl stearate, vinyl pivalate, or vinyl versatate.

[0054] The degree of polymerization of EVOH is preferably 300 to 3000. If the degree of polymerization is less than 300, the barrier property is likely to decrease, and if it exceeds 3000, the viscosity is too high and the coating suitability is likely to decrease. The degree of saponification of the vinyl ester component of EVOH is preferably 90 mol % or more, more preferably 95 mol % or more, and even more preferably 99 mol % or more. The degree of saponification of EVOH may be 100 mol % or less, or 99.9 mol % or less. The degree of saponification of EVOH is determined by nuclear magnetic resonance (1H-NMR) measurement, from the peak area of ​​hydrogen atoms contained in the vinyl ester structure and the peak area of ​​hydrogen atoms contained in the vinyl alcohol structure.

[0055] The ethylene unit content of EVOH is 10 mol% or more, more preferably 15 mol% or more, even more preferably 20 mol% or more, and particularly preferably 25 mol% or more. The ethylene unit content of EVOH is preferably 65 mol% or less, more preferably 55 mol% or less, and even more preferably 50 mol% or less. When the ethylene unit content is 10 mol% or more, the gas barrier property or dimensional stability can be maintained well under high humidity. On the other hand, when the ethylene unit content is 65 mol% or less, the gas barrier property can be improved. The ethylene unit content of EVOH can be determined by NMR method.

[0056] When a polyvinyl alcohol resin is used as the anchor coat layer 32a, the anchor coat layer 32a can be formed by coating a polyvinyl alcohol resin solution, multi-layer extrusion, or the like.

[0057] (Vapor deposited layer 32b) The deposition layer 32b is a layer (gas barrier layer) that exhibits gas barrier properties against water vapor and oxygen, and contains at least one of a metal and an inorganic oxide. The deposition layer 32b is provided directly on the anchor coat layer 32a. The deposition layer 32b may have a single-layer structure or a laminated structure. Therefore, the deposition layer 32b contains at least one of a metal deposition layer and an inorganic oxide layer. When the deposition layer 32b includes a metal deposition layer, examples of the metal included in the metal deposition layer include aluminum and stainless steel. When the deposition layer 32b includes an inorganic oxide layer, examples of the inorganic oxide included in the inorganic oxide layer include aluminum oxide, silicon oxide, magnesium oxide, and tin oxide. From the viewpoints of transparency and barrier properties, the inorganic oxide may be selected from the group consisting of aluminum oxide, silicon oxide, and magnesium oxide. In addition, the inorganic oxide layer is preferably a layer using silicon oxide from the viewpoint of excellent tensile stretchability during processing. By using an inorganic oxide layer, high barrier properties can be obtained with a very thin layer within a range that does not affect the recyclability of the laminate 1.

[0058] When the deposition layer 32b is an inorganic oxide layer using silicon oxide, the O / Si ratio of the inorganic oxide layer is preferably 1.7 or more. When the O / Si ratio is 1.7 or more, the content ratio of metal Si is suppressed, and good transparency is easily obtained. In addition, the O / Si ratio is preferably 2.0 or less. When the O / Si ratio is 2.0 or less, the crystallinity of SiO is high, and the inorganic oxide layer can be prevented from becoming too hard, and good tensile resistance is obtained. This makes it possible to suppress the occurrence of cracks in the inorganic oxide layer when the barrier coat layer 32c is laminated. In addition, even after forming into a packaging bag, the first base layer 10 may shrink due to heat during boiling or retort treatment, but when the O / Si ratio is 2.0 or less, the inorganic oxide layer easily follows the above shrinkage, and the deterioration of the barrier property can be suppressed. From the viewpoint of obtaining these effects more fully, the O / Si ratio of the inorganic oxide layer is preferably 1.75 to 1.9, and more preferably 1.8 to 1.85.

[0059] When the deposition layer 32b is an inorganic oxide layer using silicon oxide, the O / Si ratio of the inorganic oxide layer can be determined by X-ray photoelectron spectroscopy (XPS). For example, the measurement can be performed using an X-ray photoelectron spectrometer (manufactured by JEOL Ltd., product name: JPS-90MXV) as a measuring device, a non-monochromated MgKα (1253.6 eV) X-ray source, and an X-ray output of 100 W (10 kV-10 mA). For quantitative analysis to determine the O / Si ratio, relative sensitivity factors of 2.28 for O1s and 0.9 for Si2p can be used.

[0060] The thickness of the deposition layer 32b is, for example, 5 nm or more and 80 nm or less. When the thickness of the deposition layer 32b is 5 nm or more, sufficient water vapor barrier properties can be obtained. When the thickness of the deposition layer 32b is 80 nm or less, the occurrence of cracks due to deformation caused by internal stress of the thin film can be suppressed, and the deterioration of the water vapor barrier properties can be suppressed. Note that, when the thickness of the deposition layer 32b exceeds 80 nm, costs tend to increase due to an increase in the amount of material used and a prolonged film formation time, and this is not preferable from an economical point of view. From the same viewpoint as above, the thickness of the deposition layer 32b may be 20 nm or more and 40 nm or less.

[0061] The deposition layer 32b can be formed by, for example, vacuum deposition. In the vacuum deposition, physical vapor deposition or chemical vapor deposition can be used. Examples of physical vapor deposition include, but are not limited to, vacuum deposition, sputtering, and ion plating. Examples of chemical vapor deposition include, but are not limited to, thermal CVD, plasma CVD, and photo CVD.

[0062] In the vacuum film formation, resistance heating vacuum deposition, EB (Electron Beam) heating vacuum deposition, induction heating vacuum deposition, sputtering, reactive sputtering, dual magnetron sputtering, plasma enhanced chemical vapor deposition (PECVD), etc. are particularly preferably used. However, in terms of productivity, the vacuum deposition is currently the most superior. As a heating means for the vacuum deposition, it is preferable to use any of the electron beam heating method, resistance heating method, and induction heating method.

[0063] (Barrier coat layer 32c) The barrier coat layer 32c is a coating layer having gas barrier properties (gas barrier coating layer) and is provided on the deposition layer 32b. When the gas barrier layer 32 has the barrier coat layer 32c, the adhesion between the sealant layer 50 and the intermediate layer 30 via the second adhesive layer 40 tends to be high. This allows the internal pressure applied to the sealant layer 50 to be distributed throughout the laminate 1. As a result, the packaging bag obtained from the laminate 1 is less likely to break due to pressure from the inside of the packaging bag. The barrier coat layer 32c is a layer formed using a composition for forming a gas barrier coating layer (hereinafter also referred to as a coating agent) containing at least one selected from the group consisting of a hydroxyl group-containing polymer compound, a metal alkoxide, a silane coupling agent, and a hydrolyzate thereof.

[0064] From the viewpoint of more fully maintaining the gas barrier property after hot water treatment such as retort treatment, the coating agent preferably contains at least a silane coupling agent or a hydrolyzate thereof, more preferably contains at least one selected from the group consisting of a hydroxyl group-containing polymer compound, a metal alkoxide and their hydrolyzates, and a silane coupling agent or a hydrolyzate thereof, and further preferably contains a hydroxyl group-containing polymer compound or a hydrolyzate thereof, a metal alkoxide or a hydrolyzate thereof, and a silane coupling agent or a hydrolyzate thereof. The coating agent can be prepared, for example, by mixing a metal alkoxide and a silane coupling agent directly or after being previously hydrolyzed, into a solution in which a hydroxyl group-containing polymer compound, which is a water-soluble polymer, is dissolved in an aqueous (water or water / alcohol mixture) solvent.

[0065] Each component contained in the coating agent for forming the barrier coat layer 32c will be described in detail. Examples of hydroxyl-containing polymer compounds used in the coating agent include polyvinyl alcohol, polyvinylpyrrolidone, starch, methyl cellulose, carboxymethyl cellulose, sodium alginate, etc. Among these, polyvinyl alcohol (PVA) is preferably used in the coating agent for the barrier coat layer 32c because it has particularly excellent gas barrier properties.

[0066] From the viewpoint of obtaining excellent gas barrier properties, the barrier coat layer 32c is preferably formed from a composition containing at least one selected from the group consisting of metal alkoxides represented by the following general formula (I) and hydrolysates thereof. M(OR 1 ) m (R 2 ) n-m …(I) In the above general formula (I), R 1 and R 2 are each independently a monovalent organic group having 1 to 8 carbon atoms, and are preferably an alkyl group such as a methyl group or an ethyl group. M represents an n-valent metal atom such as Si, Ti, Al, or Zr. m is an integer from 1 to n. 1 or R2 If there are multiple, R 1 Friends or R 2 They may be the same or different.

[0067] Specific examples of metal alkoxides include tetraethoxysilane [Si(OC2H5)4], triisopropoxyaluminum [Al(O-2'-C3H7)3], etc. Tetraethoxysilane and triisopropoxyaluminum are preferred because they are relatively stable in aqueous solvents after hydrolysis.

[0068] The silane coupling agent includes a compound represented by the following general formula (II). Si(OR 11 ) p (R 12 ) 3-p R 13 …(II) In the above general formula (II), R 11 represents an alkyl group such as a methyl group or an ethyl group, and R 12 represents a monovalent organic group such as an alkyl group, an aralkyl group, an aryl group, an alkenyl group, an alkyl group substituted with an acryloxy group, or an alkyl group substituted with a methacryloxy group, and R 13 represents a monovalent organic functional group, and p represents an integer of 1 to 3. 11 or R 12 If there are multiple, R 11 Friends or R 12 R may be the same or different. 13 Examples of the monovalent organic functional group represented by the formula (I) include a monovalent organic functional group containing a glycidyloxy group, an epoxy group, a mercapto group, a hydroxyl group, an amino group, an alkyl group substituted with a halogen atom, or an isocyanate group.

[0069] Specific examples of the silane coupling agent include vinyltrimethoxysilane, γ-chloropropylmethyldimethoxysilane, γ-chloropropyltrimethoxysilane, glycidoxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, and γ-methacryloxypropylmethyldimethoxysilane.

[0070] The silane coupling agent may also be a polymer formed by polymerizing the compound represented by the general formula (II). The polymer is preferably a trimer, more preferably 1,3,5-tris(3-trialkoxysilylalkyl)isocyanurate. This is a condensation polymer of 3-isocyanate alkylalkoxysilane. It is known that the isocyanate moiety of this 1,3,5-tris(3-trialkoxysilylalkyl)isocyanurate is chemically non-reactive, but the reactivity is ensured by the polarity of the nurate moiety. In general, it is added to adhesives, etc., in the same manner as 3-isocyanate alkylalkoxysilane, and is known as an adhesion improver. Therefore, by adding 1,3,5-tris(3-trialkoxysilylalkyl)isocyanurate to a hydroxyl group-containing polymer compound, the water resistance of the gas barrier coating layer can be improved by hydrogen bonding. 3-isocyanate alkyl alkoxysilanes are highly reactive and have low liquid stability, whereas 1,3,5-tris(3-trialkoxysilylalkyl)isocyanurates are not water-soluble due to the polarity of the nurate moiety, but are easily dispersed in aqueous solutions and can maintain a stable liquid viscosity. In addition, the water resistance of 3-isocyanate alkyl alkoxysilanes is equivalent to that of 1,3,5-tris(3-trialkoxysilylalkyl)isocyanurates.

[0071] 1,3,5-tris(3-trialkoxysilylalkyl)isocyanurate may be produced by thermal condensation of 3-isocyanatepropylalkoxysilane, and may contain the raw material 3-isocyanatepropylalkoxysilane, but this does not cause any problem. More preferably, 1,3,5-tris(3-trialkoxysilylpropyl)isocyanurate is used, and more preferably, 1,3,5-tris(3-trimethoxysilylpropyl)isocyanurate is used. This methoxy group has a fast hydrolysis rate, and those containing a propyl group are relatively inexpensive and therefore 1,3,5-tris(3-trimethoxysilylpropyl)isocyanurate is advantageous in practical use.

[0072] Furthermore, known additives such as an isocyanate compound, a dispersant, a stabilizer, a viscosity adjuster, and a colorant can be added to the coating agent as needed, provided that the gas barrier properties are not impaired.

[0073] The thickness of the barrier coat layer 32c is preferably 50 to 1000 nm, and more preferably 100 to 500 nm. If the thickness of the barrier coat layer 32c is 50 nm or more, there is a tendency that more sufficient gas barrier properties can be obtained, and if it is 1000 nm or less, there is a tendency that sufficient flexibility can be maintained.

[0074] The coating liquid for forming the barrier coat layer 32c can be applied by, for example, a dipping method, a roll coating method, a gravure coating method, a reverse gravure coating method, an air knife coating method, a comma coating method, a die coating method, a screen printing method, a spray coating method, a gravure offset method, etc. The coating film obtained by applying this coating liquid can be dried by, for example, a hot air drying method, a hot roll drying method, a high frequency irradiation method, an infrared irradiation method, a UV irradiation method, or a combination thereof.

[0075] The temperature for drying the coating film may be, for example, 50 to 150° C., and is preferably 70 to 100° C. By keeping the drying temperature within the above range, the occurrence of cracks in the deposition layer 32b and the barrier coat layer 32c can be further suppressed, and excellent barrier properties can be exhibited.

[0076] The barrier coat layer 32c may be formed using a coating agent containing a polyvinyl alcohol resin and a silane compound. The coating agent may contain an acid catalyst, an alkali catalyst, a photopolymerization initiator, etc., as necessary.

[0077] The polyvinyl alcohol resin is as described above. Examples of the silane compound include a silane coupling agent, polysilazane, and siloxane, and more specifically, examples of the silane compound include tetramethoxysilane, tetraethoxysilane, glycidoxypropyltrimethoxysilane, acryloxypropyltrimethoxysilane, and hexamethyldisilazane.

[0078] [Sealant layer 50] The sealant layer 50 is a layer that imparts heat sealing properties to the laminate 1. From the viewpoint of recycling suitability of the laminate 1, the sealant layer 50 is a polyolefin film similar to the first base layer 10. In this embodiment, the sealant layer 50 has a single-layer structure and is a resin layer mainly made of polypropylene, but is not limited thereto. The sealant layer 50 may include a polypropylene film or may be made of a polypropylene film.

[0079] The polypropylene film may be an acid-modified polypropylene film obtained by graft-modifying polypropylene with an unsaturated carboxylic acid, an acid anhydride of an unsaturated carboxylic acid, an ester of an unsaturated carboxylic acid, etc. As the polypropylene, a polypropylene-based resin such as a homopolypropylene resin (PP), a propylene-ethylene random copolymer, a propylene-ethylene block copolymer, or a propylene-α-olefin copolymer can be used.

[0080] The polypropylene film constituting the sealant layer 50 is preferably a non-oriented polypropylene film from the viewpoint of improving the sealing performance by heat sealing.

[0081] The polypropylene film constituting the sealant layer 50 may contain various additives such as a flame retardant, a slip agent, an antiblocking agent, an antioxidant, a light stabilizer, a tackifier, and an antistatic agent.

[0082] The thickness of the sealant layer 50 is determined depending on the weight of the contents, the shape of the packaging bag, etc., but may be generally 30 to 150 μm, or may be 50 to 80 μm.

[0083] When the sealant layer is heated in an oven at 150°C for 15 minutes, the MD heat shrinkage calculated by the above formula (1) is preferably 0.9% or less, more preferably 0.4% or less, since the oxygen barrier property after retort treatment is further superior. When the sealant layer is heated in an oven at 150°C for 15 minutes, the TD heat shrinkage calculated by the above formula (2) is preferably 0.5% or less, since the oxygen barrier property after retort treatment is further superior. The MD heat shrinkage may be, for example, 0.1% or more. The TD heat shrinkage may be, for example, 0.2% or more.

[0084] The sealant layer 50 can be formed by any of the known lamination methods, such as a dry lamination method in which a film-like sealant layer made of the above-mentioned polypropylene is bonded with an adhesive such as a one-component curing or two-component curing urethane adhesive, a non-solvent dry lamination method in which a film-like sealant layer is bonded using a solvent-free adhesive, and an extrusion lamination method in which the above-mentioned polypropylene is heated and melted, extruded into a curtain shape, and bonded together.

[0085] Among the above-mentioned forming methods, the dry lamination method is preferred because it has high resistance to retort treatment, particularly high-temperature hot water treatment at 120° C. or higher. On the other hand, if the packaging bag is used for an application in which it is treated at a temperature of 85° C. or lower, the lamination method is not particularly limited.

[0086] The total mass ratio of polypropylene in the laminate 1 is 90% by mass or more. This allows the laminate 1 to be said to be a mono-material packaging material made of a single material, and has excellent recyclability. From the viewpoint of further improving recyclability, the polyolefin content in the laminate 1 may be 92.5% by mass or more, or may be 95% by mass or more, based on the total amount of the laminate 1.

[0087] Although the gas barrier laminate according to one embodiment has been described above, the gas barrier laminate according to the present disclosure is not limited to the above embodiment. For example, the gas barrier laminate may further include a print layer.

[0088] [Print layer] The printing layer can be provided, for example, on at least one surface of the first base layer 10. The printing layer is provided at a position visible from the outside of the laminate 1 for the purpose of displaying information about the contents, identifying the contents, improving concealment, or improving the design of the packaging bag. The printing method and printing ink are not particularly limited, and are appropriately selected from known printing methods and printing inks in consideration of printability on the film, design such as color tone, adhesion, safety as a food container, and the like. Examples of printing methods that can be used include gravure printing, offset printing, gravure offset printing, flexographic printing, and inkjet printing. Among them, gravure printing can be preferably used from the viewpoints of productivity and high resolution of the pattern. Examples of resins constituting the printing layer include urethane resins, copolymer resins of vinyl chloride and vinyl acetate, and acrylic resins.

[0089] In order to improve the adhesion of the printed layer, the surface of the layer on which the printed layer is to be formed may be subjected to various pretreatments such as corona treatment, plasma treatment, and frame treatment, or a coating layer such as an easy-adhesion layer may be provided.

[0090] In addition, the gas barrier laminate of the present disclosure may not include the anchor coat layer 32a. The gas barrier laminate of the present disclosure may not include the deposition layer 32b. The gas barrier laminate of the present disclosure may not include the barrier coat layer 32c. The stacking order of the anchor coat layer 32a, the deposition layer 32b, and the barrier coat layer 32c may be reversed. In addition, the gas barrier laminate of the present disclosure may not include the first adhesive layer 20.

[0091] <Packaging bag> A packaging bag according to one embodiment will be described below. Fig. 2 is a schematic plan view of an example of the packaging bag according to this embodiment. The packaging bag 100 includes a laminate 1. The packaging bag 100 is formed into a bag shape, for example, by sealing the ends of the laminate 1 that has been folded in half.

[0092] The packaging bag 100 is a three-sided bag having a main body 101 in which the contents are accommodated, a folded portion 102 in which the laminate 1 is folded, and a sealed portion 103 located at an end of the main body 101. The shape of the main body 101 is not particularly limited, and may be rectangular when viewed from a predetermined direction. At least a part of the outer surface of the main body 101 may be printed. The main body 101 may accommodate a specific gas such as nitrogen in addition to the contents. The sealed portion 103 is a portion where a part of the sealant layer 50 of the laminate 1 and another part are bonded together. In the sealed portion 103, a part of the sealant layer 50 of the laminate 1 and another part are in close contact with each other. The sealed portion 103 is formed, for example, by heating and compressing (i.e., heat sealing) a part of the sealant layer 50 of the laminate 1 and another part, but is not limited thereto. For example, the sealed portion 103 may be formed by cold sealing or the like. In the packaging bag 100, the folded portion 102 forms one side of the main body portion 101, and the sealed portion 103 forms the remaining three sides of the main body portion 101. Both ends of the folded portion 102 and the sealed portion 103 overlap each other.

[0093] The packaging bag 100 may be used for purposes requiring heat treatment at 80° C. or higher. Examples of heat treatment include retort treatment and boiling treatment.

[0094] Retort processing is a method of sterilizing microorganisms such as mold, yeast, and bacteria by heating and pressurizing them to preserve foods, medicines, etc. In general, a packaging bag containing food, etc. is heated and pressurized at 105 to 140°C, 0.15 to 0.30 MPa, and 10 to 120 minutes. There are two types of retort devices: a steam type that uses heated steam and a hot water type that uses pressurized heated water, and they are used appropriately depending on the sterilization conditions of the contents, such as food. Boiling processing is a method of moist heat sterilization to preserve foods, medicines, etc. Usually, depending on the contents, a packaging bag containing food, etc. is moist heat sterilized at 60 to 100°C, atmospheric pressure, and 10 to 120 minutes. Boiling processing is usually performed using a hot water bath at 100°C or less. There are two types of methods: a batch type in which the bag is immersed in a hot water bath at a constant temperature and treated for a certain period of time, and then removed, and a continuous type in which the bag is passed through a hot water bath in a tunnel-like manner.

[0095] Although the packaging bag according to one embodiment has been described above, the packaging bag of the present disclosure is not limited to the above embodiment. For example, the packaging bag may be a standing pouch-shaped packaging bag, a two-sided bag, a four-sided bag, a palm-shaped bag, or a gusset bag.

[0096] <Package> A package according to one embodiment will be described below. The package is obtained by putting contents in a packaging bag 100. That is, the package includes the packaging bag 100 and the contents put in the packaging bag. The package may be one that has been subjected to a retort treatment.

[0097] The contents include, for example, food and medicine.

[0098] The elastic modulus of the second adhesive layer 40 of the packaging bag 100 is 50 MPa or less. The elastic modulus of the second adhesive layer 40 of the packaging bag 100 may be similar to the elastic modulus of the second adhesive layer 40 after the laminate 1 is subjected to a heating and pressurizing treatment (conditions: temperature 128°C, time 15 minutes, pressure 0.3 MPa). The elastic modulus of the second adhesive layer 40 of the packaging bag 100 is determined in the same manner as the elastic modulus of the second adhesive layer 40 of the laminate 1.

[0099] The elastic modulus of the first adhesive layer 20 of the packaging bag 100 may be similar to the elastic modulus of the first adhesive layer 20 after a heating and pressurizing treatment (conditions: temperature 128°C, time 15 minutes, pressure 0.3 MPa) is performed on the laminate 1. The elastic modulus of the first adhesive layer 20 of the packaging bag 100 is determined in the same manner as the elastic modulus of the first adhesive layer 20 of the laminate 1. EXAMPLES

[0100] Examples of the present disclosure will be specifically described below, however, the present disclosure is not limited to the following examples.

[0101] <First Base Layer and Second Base Layer> The following materials were prepared: OPP(A): Biaxially oriented polypropylene film (thickness 20μm) OPP(B): Biaxially oriented polypropylene film (thickness 20μm) OPP(C): Biaxially oriented polypropylene film (thickness 20 μm) OPP(D): Biaxially oriented polypropylene film (thickness 20μm)

[0102] <Sealant layer> The following materials were prepared: ·CPP(A): Non-oriented polypropylene film (thickness 60μm) ·CPP(B): Non-oriented polypropylene film (thickness 60μm)

[0103] <Adhesive layer> The following materials were prepared: Adhesive (A): Two-component urethane adhesive, mass ratio of base agent to hardener (base agent:hardener) = 6:1, main component of hardener: 1,6-diisocyanatohexane polymer Adhesive (B): Two-component urethane adhesive, mass ratio of base agent to hardener (base agent:hardener) = 7.4:1, main component of hardener: isophorodiisocyanate (IPDI) The term "major component" means a component that accounts for more than 50 mass % based on the total amount of the curing agent.

[0104] <Preparation of anchor coat layer forming composition> A mixed solution was produced by mixing and stirring γ-isocyanatepropyltrimethoxysilane:acrylic polyol at a ratio of 1:5. Next, tolylene diisocyanate (TDI) was added to the mixed solution so that the number of NCO groups of tolylene diisocyanate was equal to the number of OH groups of the acrylic polyol. Then, the mixed solution was diluted with ethyl acetate to 2% by mass. In this way, an anchor coat layer forming composition (anchor coat agent) was prepared.

[0105] <Preparation of coating solution for barrier coat layer> The following liquids A, B, and C were prepared in amounts of 10 g each and mixed to prepare a coating liquid. Liquid A: A hydrolysis solution with a solid content of 5 mass% (SiO2 equivalent) obtained by adding 72.1 g of 0.1N hydrochloric acid to 17.9 g of tetraethoxysilane (Si(OC2H5)4) and 10 g of methanol and stirring for 30 minutes. Liquid B: 5% by mass solution of polyvinyl alcohol in water / methanol (mass ratio of water:methanol is 95:5). Liquid C: A hydrolysis solution in which 1,3,5-tris(3-trialkoxysilylpropyl)isocyanurate was diluted with a mixture of water and isopropyl alcohol (water:isopropyl alcohol mass ratio 1:1) to a solid content of 5 mass%.

[0106] <Production of Gas Barrier Laminate> Example 1 The composition for forming an anchor coat layer was applied onto one main surface of the OPP (D) (second base layer) to form a coating film, and the coating film was dried at 60°C. As a result, the coating amount was 0.1 g / m 2 Next, a transparent deposition layer (silica deposition layer) made of silicon oxide having a thickness of 30 nm was formed using a vacuum deposition apparatus using an electron beam heating method.

[0107] Next, a coating liquid was applied onto the deposition layer using a bar coater to form a coating film. The coating film was dried at 100°C to form a barrier coat layer with a thickness of 300 nm on the deposition layer. This resulted in a first laminate (layer configuration: second substrate layer, anchor coat layer, deposition layer, and barrier coat layer).

[0108] A printed layer was formed on one main surface of OPP (A) (first base layer). The first laminate and OPP (A) were bonded together via adhesive (A) so that the second base layer and the printed layer faced each other. The adhesive (A) was cured at 40°C for 96 hours to form a first adhesive layer. This resulted in a second laminate (layer structure: first base layer, printed layer, first adhesive layer, second base layer, anchor coat layer, vapor deposition layer, and barrier coat layer).

[0109] The second laminate and CPP (A) (sealant layer) were bonded together via adhesive (A) so that the barrier coat layer and the sealant layer faced each other. The adhesive (A) was cured (curing temperature: 40°C, curing time: 96 hours) to form a second adhesive layer. This resulted in a gas barrier laminate (layer structure: first base layer, printed layer, first adhesive layer, second base layer, anchor coat layer, vapor deposition layer, barrier coat layer, second adhesive layer, and sealant layer).

[0110] Example 2 A gas barrier laminate was obtained in the same manner as in Example 1, except that OPP (B) was used as the first base layer.

[0111] Comparative Example 1 A gas barrier laminate was obtained in the same manner as in Example 1, except that the adhesive (B) was used as the first adhesive layer and the second adhesive layer, the curing temperature was 40° C., and the curing time was 120 hours.

[0112] Comparative Example 2 A gas barrier laminate was obtained in the same manner as in Comparative Example 1, except that OPP (B) was used as the first base layer.

[0113] Comparative Example 3 A gas barrier laminate was obtained in the same manner as in Comparative Example 1, except that OPP (C) was used as the first base layer and CPP (B) was used as the sealant layer.

[0114] Comparative Example 4 A first laminate was obtained in the same manner as in Example 1. A printed layer was formed on one main surface of OPP (B) (first base layer). The first laminate and OPP (B) were bonded together via adhesive (A) so that the barrier coat layer and the printed layer faced each other. A first adhesive layer was formed by curing the adhesive (A) in the same manner as in Example 1. This resulted in a second laminate (layer structure: first base layer, printed layer, first adhesive layer, barrier coat layer, vapor deposition layer, anchor coat layer, and second base layer).

[0115] The second laminate and CPP (A) (sealant layer) were bonded together via the adhesive (A) so that the second base layer and the sealant layer faced each other. The adhesive (A) was cured to form a second adhesive layer in the same manner as in Example 1. This resulted in a gas barrier laminate (layer structure: first base layer, printed layer, first adhesive layer, barrier coat layer, vapor deposition layer, anchor coat layer, second base layer, second adhesive layer, and sealant layer).

[0116] Comparative Example 5 A gas barrier laminate was obtained in the same manner as in Comparative Example 4, except that the adhesive (B) was used as the first adhesive layer and the second adhesive layer, the curing temperature was 40° C., and the curing time was 120 hours.

[0117] <Manufacturing of packaging bags> Using the laminates of each of the Examples and Comparative Examples, packaging bags having four sealed sides were produced.

[0118] <Retort processing> Water was filled into the packaging bag of each of the Examples and Comparative Examples to obtain a package. The package was placed in the furnace of a retort device and subjected to retort treatment (128°C, 15 minutes, 0.3 MPa). The retort treatment was performed by spraying the package with water in a shower from a spray nozzle in the furnace.

[0119] <Measurement of polyethylene resin content> The total mass ratio of polypropylene in the gas barrier laminates obtained in each of the Examples and Comparative Examples was measured, and as a result, the total mass ratio of polypropylene in all of the gas barrier laminates was 90 mass % or more.

[0120] <Measurement of Heat Shrinkage of First Base Layer, Second Base Layer, and Sealant Layer> The thermal shrinkage rates of the first base material layer, the second base material layer and the sealant layer of each of the Examples and Comparative Examples were measured according to the following procedure. The results are shown in Table 1.

[0121] As shown in FIG. 3(a), the substrate or sealant layer to be measured was cut into a size of 200 mm×200 mm to prepare a measurement sample 500. (b) As shown in FIG. 3, two straight lines L1 and L2, each having a length of 120 mm or more and parallel to the TD of the measurement sample 500, were drawn with an interval of 100 mm. (c) As shown in FIG. 3, two straight lines L3 and L4, each having a length of 120 mm or more and parallel to the MD of the measurement sample 500, were drawn with an interval of 100 mm. (d) As shown in Fig. 3, seven graduations N1 to N7 were written at 20 mm intervals on the line L1. Graduations were written similarly on the lines L2 to L4. At this time, the graduations of the lines L1 and L2 were positioned so that when each of the graduations N1 to N7 on the line L1 was connected to each of the graduations N1 to N7 on the line L2, the lines were parallel to MD. Furthermore, the graduations of the lines L3 and L4 were positioned so that when each of the graduations N1 to N7 on the line L3 was connected to each of the graduations N1 to N7 on the line L4, the lines were parallel to TD. (e) The measurement sample 500 placed on a Teflon (registered trademark) sheet was placed on a glass plate in an oven heated to a predetermined temperature (150° C.) and heated for 15 minutes. After heating, the measurement sample 500 was removed from the oven and left at room temperature (25° C.) for 30 minutes. (f) The linear distance between the scale N1 (intersection of L1 and N1) of the straight line L1 and the scale N1 (intersection of L2 and N1) of the straight line L2 was measured as the MD length before and after heating, and the MD heat shrinkage was calculated by the following formula (1). Similarly, the MD heat shrinkage was calculated at each position of the scales N1 to N7, and the average value of these was determined as the MD heat shrinkage of the measurement sample 500. MD heat shrinkage rate (%) = (MD length before heating - MD length after heating) / MD length before heating × 100 ... (1) (g) The linear distance between the scale N1 of the straight line L3 (intersection of L3 and N1) and the scale N1 of the straight line L4 (intersection of L4 and N1) was measured as the TD length before and after heating, and the TD heat shrinkage was calculated by the following formula (2). Similarly, the TD heat shrinkage was calculated at each position of the scales N1 to N7, and the average value of these was determined as the TD heat shrinkage of the measurement sample 500. TD heat shrinkage rate (%) = (TD length before heating - TD length after heating) / TD length before heating × 100 ... (2)

[0122] <Measurement of elastic modulus of the second adhesive layer> (No retort treatment) An epoxy adhesive (product name: Bond E Set, manufactured by Konishi Co., Ltd.) was applied to the main surface of the first base layer of the laminate produced in each of the Examples and Comparative Examples. Then, the laminate was attached to a glass plate via the epoxy adhesive to form a sample having a laminate smoothly fixed to the glass plate.

[0123] After the epoxy adhesive hardened, the sample was placed on an oblique cutting device (manufactured by Daipla Wintes Co., Ltd., product name: SAICAS DN-GS). Next, a diamond cutting blade with a V-shaped tip was attached to the oblique cutting device, and side cut lines were applied to the surface of the sealant layer at 1 mm intervals. Next, a diamond knife with a blade width of 1 mm, a rake angle of 20 degrees, and a clearance angle of 10 degrees was contacted with the surface of the sealant layer with a load of 0.05 N, and then the sealant layer was obliquely cut at a horizontal speed of 50 μm / s and a vertical speed of 1 μm / s. At this time, first, after the cutting depth reached 55 μm, it was cut horizontally for 10 mm. Next, finish cutting was performed at a cutting depth of 1 μm under conditions of a horizontal speed of 50 μm / s and a vertical speed of 1 μm / s. The exposed surface after cutting was observed, and the number of finish cuts was added as necessary until the desired exposed surface of the second adhesive layer was obtained. As a result of the above, the second adhesive layer was exposed.

[0124] A force curve of the second adhesive layer was measured using a scanning probe microscope to obtain a graph showing the relationship between the deformation amount of the second adhesive layer and the load applied to the second adhesive layer. The elastic modulus of the second adhesive layer was calculated from the obtained graph based on the JKR analysis model. The measurement device, measurement conditions, and analysis conditions were as follows. The results are shown in Table 2.

[0125] (Device) Scanning probe microscope MFP-3D (Oxford Instruments) (Cantilever) Model number: Biosphere B30-FM (manufactured by Nanotools) Tip material: Diamond-like carbon Radius of curvature: 35nm (Measurement conditions) Maximum load: 5nN (test depth is 20~30nm) Test speed: 500nm / sec (Analysis conditions) Analysis model: JKR model Analysis domain: Pull-out domain Analysis range: Load 0 to 80% (percentage of minimum to maximum value) Poisson's ratio of sample: 0.33

[0126] (Retort processing available) A laminate was cut out from the packaging bag after the retort treatment of each Example and Comparative Example. The elastic modulus of the second adhesive layer was measured using the cut out laminate in the same manner as in the case without the retort treatment. The results are shown in Table 2.

[0127] <Bursting strength> Air was gradually injected into the packaging bags before and after retort treatment. The pressure was measured at the moment the air leaked from the sealed area. A burst strength tester (Sun Scientific Co., Ltd. 305-BP-J) was used for the measurements. The measurement results were evaluated according to the following criteria. The results are shown in Table 2. (standard) A: The pressure at the moment air leaks before retort processing is 1.1 bar or more, and the pressure at the moment air leaks after retort processing is 0.95 bar or more. B: Anything other than A above

[0128] <Oxygen permeability measurement> A laminate was cut out from the packaging bag after retort treatment of each of the Examples and Comparative Examples. The oxygen permeability of the cut-out laminate was measured using an oxygen permeability measuring device (manufactured by MOCON, device name: OXTRAN 2 / 21). The measurement atmosphere was 23°C and 70% RH. The measurement results were evaluated according to the following criteria. The results are shown in Table 2. (standard) A: Oxygen permeability is 1.5 [cc / m 2 / day] or less B: Anything other than A above

[0129] [Table 1]

[0130] [Table 2] [Explanation of symbols]

[0131] Reference Signs List: 1...laminate, 10...first substrate layer, 20...first adhesive layer, 30...intermediate layer, 31...second substrate layer, 32...gas barrier layer, 32a...anchor coat layer, 32b...vapor deposition layer, 32c...barrier coat layer, 40...second adhesive layer, 50...sealant layer, 100...packaging bag.

Claims

1. A first substrate layer; an intermediate layer having a second base layer and a gas barrier layer provided on a surface of the second base layer; An adhesive layer; A sealant layer; A gas barrier laminate having a layered structure comprising the above in this order, the gas barrier layer is located between the second base layer and the adhesive layer, The total mass ratio of polypropylene in the laminate is 90 mass% or more, A gas barrier laminate, wherein the adhesive layer has an elastic modulus of 30 MPa or less, as determined through the following steps (a) and (b): <Measurement of Elastic Modulus> (a) A step of obtaining a graph showing the relationship between the deformation amount of the adhesive layer and the load applied to the adhesive layer by measuring a force curve of the adhesive layer using a scanning probe microscope. (b) calculating the elastic modulus of the adhesive layer from the graph based on a JKR analysis model;

2. 2. The gas barrier laminate according to claim 1, wherein the elastic modulus of the adhesive layer determined through the steps (a) and (b) after carrying out a heating and pressurizing treatment under conditions of a temperature of 128°C, a time of 15 minutes, and a pressure of 0.3 MPa is 50 MPa or less.

3. The gas barrier laminate according to claim 1 , wherein the gas barrier layer has a barrier coat layer.

4. The gas barrier laminate according to claim 3 , wherein the gas barrier layer comprises, from the second base layer side, an anchor coat layer, a vapor deposition layer, and the barrier coat layer in this order.

5. The gas barrier laminate according to claim 4 , wherein the vapor deposition layer has a thickness of 5 nm or more and 80 nm or less.

6. When the first base layer is heated in an oven at 150° C. for 15 minutes, the heat shrinkage rate in MD calculated by the following formula (1) is 7% or less, and the heat shrinkage rate in TD calculated by the following formula (2) is 5% or less, 2. The gas barrier laminate according to claim 1, wherein when the sealant layer is heated in an oven at 150° C. for 15 minutes, the MD heat shrinkage percentage calculated by the following formula (1) is 0.4% or less: MD heat shrinkage rate (%) = (MD length before heating - MD length after heating) / MD length before heating × 100 ... (1) TD heat shrinkage rate (%) = (TD length before heating - TD length after heating) / TD length before heating × 100 ... (2)

7. 2. The gas barrier laminate according to claim 1, wherein the adhesive layer has a thickness of 0.5 μm or more and 10 μm or less.

8. The first base layer and the second base layer are stretched polypropylene films, The gas barrier laminate according to claim 1 , wherein the sealant layer is a non-oriented polypropylene film.

9. A packaging bag formed using the gas barrier laminate according to any one of claims 1 to 8.

10. The packaging bag according to claim 9, which is used for applications in which a heat treatment of 80°C or more is performed.

11. A packaging bag and contents contained in the packaging bag. The packaging bag is formed using a laminate, the laminate has a laminate structure including, in this order, a first base material layer, an intermediate layer having a second base material layer and a gas barrier layer provided on a surface of the second base material layer, an adhesive layer, and a sealant layer; The total mass ratio of polypropylene in the laminate is 90 mass% or more, A package, wherein the adhesive layer has an elastic modulus of 50 MPa or less, as determined through the following steps (a) and (b): <Measurement of Elastic Modulus> (a) A step of obtaining a graph showing the relationship between the deformation amount of the adhesive layer and the load applied to the adhesive layer by measuring a force curve of the adhesive layer using a scanning probe microscope. (b) calculating the elastic modulus of the adhesive layer from the graph based on a JKR analysis model;

Citation Information

Patent Citations

  • Laminate and packaging bag

    JP2021020391A

Cited By

  • Laminate, packaging bag, and packaging body

    WO2026211430A1